Experience of using unmanned aerial photography systems for mapping the territory of the Russian Federation - S. Nekhin; A. Rubenok (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The analysis of the methods of remote sensing of the Earth (remote sensing) used in mapping the territory of the Russian Federation (satellite imagery, aerial photography from manned and unmanned aerial vehicles - UAVs) is given. The economic, technical and organizational factors influencing the choice of remote sensing method for the purposes of mapping the territory of the country indicated. The advantages of the UAV method are shown. These advantages include lower financial costs of carrying out cartographic works in limited areas, the speed of surveying and obtaining images, the ability to survey from low altitudes, including under low clouds, and obtain high-resolution images. The disadvantages of surveying using UAV include lower productivity on large survey area, restrictions on access to certain territories (depending on terrain, remoteness, and other obstacles), limitations in the ability to install additional equipment to improve the quality and capabilities of aerial survey materials, and increased insurance risk of use. At the same time, taking into account all the positive and negative factors, there is a tendency for the gradual outstripping development of aerial photography from the UAV. Along with the progress in the development of UAVs, this is facilitated by the current situation in the country with a decreasing number of manned aircraft used for aerial photography. Important conditions and the main factors stimulating the UAV demand for their successful implementation and use are improving the quality, reliability, safety and warranty period of UAV operation, development and production of aerial photography equipment for UAV. An important role is also given to changes in legislation that favor the use of UAV, the partial replacement of the aging fleet of manned aircraft used for aerial photography with unmanned systems. The main characteristics of unmanned aerial vehicles of light and medium type necessary for solving production tasks in the field of cartography and cadastre are specified. The main characteristics of on-board equipment for light and medium-type of unmanned aircraft system (UAS) necessary to meet production tasks are given, as well as the main technical requirements for light and medium-type UAS software. The features of photogrammetric processing of remote sensing data obtained with the help of UAS, the need to perform research tests of complexes of technical and software tools for digital aerial photography and photogrammetric processing based on the use of UAS are noted. The conclusion contains findings and recommendations.